Phosphorus and Manganese Effect on Oxygen-Consumption of Coal Spontaneous Combustion - Tang, Yibo; Li, Zenghua; Yang, Yongliang; Ma, Dongjuan (Asian Journal of Chemistry, 2013)
Effects of two kinds of trace elements (manganese and phosphorus) on coal spontaneous combustion are investigated in this paper. The oxygen-consumptions in oxidization of coal samples with reagents are measured. The experimental results suggest that the reagents of manganese can catalyze the coal spontaneous combustion, whereas phosphorus can inhibit the reactions. Moreover, the impact of these promoting and inhibiting regents was strengthened with an increase in the additive loading. This phenomenon can be explained by mechanism of free radical reactions to some extent.